Predicting Disease-Specific Survival for Patients With Primary Cholangiocarcinoma Undergoing Curative Resection by Using a Decision Tree Model - Quan, Bing; Li, Miao; Lu, Shenxin; Li, Jinghuan; Liu, Wenfeng; Zhang, Feng; Chen, Rongxin; Ren, Zhenggang; Yin, Xin (Frontiers in Oncology, 2022)
Background: The aim of this study was to derive and validate a decision tree model to predict disease specific survival after curative resection for primary cholangiocarcinoma (CCA). Method: 21 clinical characteristics were collected from 482 patients after curative resection for primary CCA. 289 patients were randomly allocated into a training cohort and 193 into a validation cohort. We built three decision tree models based on 4, 12, 21 variables, respectively. Area under curve (AUC), sensitivity and specificity were used for comparison of the 0.5-, 1-, and 3-year decision tree models and regression models. AUC and decision curve analysis (DCA) were used to determine the predictive performances of the 0.5-, 1-, and 3-year decision tree models and AJCC TNM stage models. Results: According to the fitting degree and the computational cost, the decision tree model derived from 12 variables displayed superior predictive efficacy to the other two models, with the accuracy of 0.955 in the training cohort and 0.782 in the validation cohort. Maximum tumor size, resection margin, lymph node status, histological differentiation, TB level, ALBI, AKP, AAPR, ALT, γ－GT, CA19-9, Child-Pugh grade were involved in the model. The performances of 0.5-, 1-, and 3-year decision tree models were better than those of conventional models and AJCC TNM stage models. Conclusion: We developed a decision tree model to predict outcomes for CCA undergoing curative resection.The present decision tree model outperformed other clinical models, facilitating individual decision-making of adjuvant therapy after curative resection.